1994
DOI: 10.1523/jneurosci.14-06-03533.1994
|View full text |Cite
|
Sign up to set email alerts
|

Hypomyelinating peripheral neuropathies and schwannomas in transgenic mice expressing SV40 T-antigen

Abstract: We have prepared transgenic mice carrying a temperature-sensitive mutant of the SV40 oncogene (tsA-1609) under the control of 5' flanking sequences from the Schwann cell-specific P0 gene. Four of six founder mice showed moderate to severe hypomyelination in peripheral nerves of tail biopsies, with only rare myelinated fibers. Offspring were obtained from three of these founders. Northern blot and immunohistochemical analyses showed that expression of T-antigen was restricted to the PNS. Mice expressing the hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
21
0

Year Published

1995
1995
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 21 publications
0
21
0
Order By: Relevance
“…The NF-Y control probe (major histocompatibility complex class II Y box sequence) bound a complex of the same mobility in Schwann cell extracts and was also supershifted by the NF-Y antibody (Fig. 7C, lanes [17][18][19][20]. Notably, this antibody did not alter the probe 4-specific doublet, C1 (lane 14) and did not supershift C1 on the probe containing site 4 alone (data not shown).…”
Section: Sequence Conservation and Promoter Deletion Analyses Reveal mentioning
confidence: 89%
See 2 more Smart Citations
“…The NF-Y control probe (major histocompatibility complex class II Y box sequence) bound a complex of the same mobility in Schwann cell extracts and was also supershifted by the NF-Y antibody (Fig. 7C, lanes [17][18][19][20]. Notably, this antibody did not alter the probe 4-specific doublet, C1 (lane 14) and did not supershift C1 on the probe containing site 4 alone (data not shown).…”
Section: Sequence Conservation and Promoter Deletion Analyses Reveal mentioning
confidence: 89%
“…Whereas C1 reflects the binding of an as yet unidentified protein, these results suggest that C2 contains transcription factor NF-Y in Schwann cell nuclear extracts. cells and are strongly up-regulated at the onset of peripheral myelination (19,20). Similarly, reporter genes linked to the same 5Ј-flanking region are transcribed at exceptionally high levels when transfected into Schwann cells but not when introduced into non-Schwann cells (18).…”
Section: Sequence Conservation and Promoter Deletion Analyses Reveal mentioning
confidence: 99%
See 1 more Smart Citation
“…Nf2 þ /À ;p53 þ /À cis mice (carrying the Nf2 and p53 mutation on the same chromosome 11) develop osteosarcomas and fibrosarcomas after a shorter latency period (5 months) than seen in either Nf2 þ /À or p53 þ /À mice. Loss of p53 may be important in tumorigenesis of P0-permissive murine cells in view of the observation that P0-SV40T antigen transgenic mice develop schwannomas (Messing et al, 1994).…”
Section: Introductionmentioning
confidence: 99%
“…Using cultures of rat Schwann cells and transgenic mice, it was shown that a 1.1-kb promoter region of the rat P 0 promoter is sufficient to mediate Schwann cell-specific expression both in vitro and in vivo (27,29,30). Transient transfections have been used to analyze this region in further detail.…”
mentioning
confidence: 99%